Partisipasi Petani dalam Pengelolaan Irigasi Berbasis Perkumpulan Petani Pemakai Air (P3A) di Kecamatan Kebakkramat Kabupaten Karanganyar - Khilda, Isna Noor; Suminah, Suminah; Permatasari, Putri (Fakultas Pertanian, Universitas Lampung, 2025)
The decline in farmer participation in irrigation management based on the Water User Farmers Association (P3A) is important to study because it impacts the performance of irrigation that serves rice fields, ultimately leading to land productivity to meet rice needs. This study aims to: (1) Study and describe the conditions for growing participation and farmer participation in P3A-based irrigation management, and (2) Analyze the influence between the conditions for growing participation on farmer participation in P3A-based irrigation management. The research method in this study uses a quantitative method. The sample consisted of 60 farmer respondents were selected using the proportionate stratified random sampling technique. The data were collected through survey techniques, interviews, and literature studies. Data analysis in this study used multiple linear regression tests using IBM SPSS Statistics 25 software. The results of the study showed that: (1) In general, the conditions for growing participation in the form of participation opportunities are relatively high, but still relatively low in the opportunity to be involved in meetings, operations, and irrigation maintenance; willingness to participate is relatively moderate; and the ability to participate is relatively high; while farmer participation in general is still relatively low; (2) These three conditions for growing simultaneously affect farmer participation in P3A-based irrigation management. Partially, opportunity and willingness have a significant influence on farmer participation, while ability does not have a significant influence on farmer participation.